APPLICATION OF THE FORECASTING METHOD TO THE DEMAND FOR PRINTING RECEIPTS WITH GTO 46 ENGINE - Sinambela, Yusnia; Siregar, Efrizal; juwairiah, Juwairiah (Kreator, 2023)
Forecasting is an important part of every business organization and for every very significant management decision. The purpose of forecasting is to reduce the risk or uncertainty faced by a company in making short-term operational decisions and in planning for long-term growth. The company that is the object of this research is a company operating in the printing sector. Focus on observing receipt products because receipt orders are the highest every month. In the implementation of the production process, there are often shortages of raw materials such as NCR paper or non-carbon required paper so that delivery times are late to reach consumers. The effort used to eliminate/reduce the gap between production and sales is to use a forecasting method which aims to determine product quantity adjustments and when they are needed. Based on data processing using cyclical and linear methods, the method used in calculating the next month's forecast is the Linear method. The linear method has the smallest error values, namely SEE = 1100.57, MAD = 871 and MAPE = 26.34. The total forecast demand for receipt products in November is 4839 pieces